2017
DOI: 10.3389/fphar.2017.00113
|View full text |Cite
|
Sign up to set email alerts
|

Anti-adipogenic Effects and Mechanisms of Ginsenoside Rg3 in Pre-adipocytes and Obese Mice

Abstract: Red or black ginseng has been reported more powerful than white/fresh ginseng in dealing with various diseases/conditions including obesity. The major reason is that heating/steaming, the process of making red or black ginseng, produces large amount of bioactive compounds including ginsenoside Rg3 (Rg3), which are trace in fresh or white ginseng. In the present study, Rg3 was applied both in pre-adipocytes and obese mice to investigate the anti-adipogenic effects and relevant mechanisms. Our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…Previous studies regarding anti-obesity effects of Rg3 have suggested that Rg3 inhibits adipogenic differentiation through AMPK activation [12,16]. We also investigated whether Rg3 activates AMPK signaling in differentiated 3T3-L1 adipocytes and found that AMPK phosphorylation was increased dose-dependently following Rg3 treatment for 24 h ( Figure 3A).…”
Section: Rg3 Induced Browning Of Differentiated 3t3-l1 Cells Via Actimentioning
confidence: 74%
See 3 more Smart Citations
“…Previous studies regarding anti-obesity effects of Rg3 have suggested that Rg3 inhibits adipogenic differentiation through AMPK activation [12,16]. We also investigated whether Rg3 activates AMPK signaling in differentiated 3T3-L1 adipocytes and found that AMPK phosphorylation was increased dose-dependently following Rg3 treatment for 24 h ( Figure 3A).…”
Section: Rg3 Induced Browning Of Differentiated 3t3-l1 Cells Via Actimentioning
confidence: 74%
“…However, processing to red ginseng and black ginseng significantly increases the Rg3 content in both American ginseng [26] and Asian ginseng [27]. Previous studies on Rg3 effects during 3T3-L1 differentiation have reported that Rg3 attenuates differentiation in 3T3-L1 cells by reducing PPAR-γ, C/EBP-α, FAS, and perilipin [12], or in regulating AMPK and PPAR-γ [16]. In this context, our results suggest the role of Rg3 in browning of mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PPD-type minor ginsenoside Rg3, a kind of saponin triterpene, shows significant anticancer properties against, for example lung cancer (Xie et al 2017;Wang et al 2019), colon cancer ), ovarian cancer (Xu et al 2007;Xu et al 2008;Zhao et al 2019) and prostate cancer (Kim et al 2010;Peng et al 2019). In addition, it has remarkable neuroprotection (Tian et al 2005;Tian et al 2009), liver protection (Lee et al 2005), antiobesity (Hwang et al 2009;Zhang et al 2017), antidiabetic (Sun and Zhou 2010;Niu et al 2012;Guo et al 2018) and vasodilatation (Kim and Nah 2005;Kim et al 2006;Jeong et al 2017) activities. Thus, ginsenoside Rg3 has a potential application in the field of medicine and food additive.…”
Section: Introductionmentioning
confidence: 99%